Evaluation of amnion versus calcium alginate as split-thickness skin graft donor site dressing: A randomised controlled trial - -E-Rasul, Roeya; Akram, Bushra; Abidin, Zain Ul; Khalid, Farrukh Aslam; Raza, Sheraz; Khalid, Kamran (Journal of Fatima Jinnah Medical University, 2022)
Background: Split-thickness skin graft (STSG) covers patient’s primary wound, but, at the expense of a donor-wound which heals by secondary intention. This study evaluated the efficacy of amnion and calcium alginate dressings at STSG donor sites in terms of healing duration, patient comfort and incidence of infection. Patients and methods: An open label randomised control trial was conducted during October 2018 to May 2019. Total 60 patients, aged 20-45 years, were randomly allocated to two equal groups. Amnion was applied to 30 donor sites in Group A and calcium alginate in 30 donor sites in Group B. Patients were phone-called on 1st, 3rd and 7th post-operative days and donor site pain scored using numerical rating scale. Donor site was opened on 10th postoperative day and signs of infection assessed. Lastly, the day on which donor site healed, revealing an epithelialized wound, was noted. Results: Group A included 30 patients (11 females, 19 males) having mean age of 31.23 years and Group B included 30 patients (12 females, 11 males) having mean age of 31.30 years. Average pain scores on 1st, 3rd and 7th post-operative days were 7.6, 6.6 and 4.4 in Group A and it was 8.2, 6.5 and 4.4 in Group B. Two cases of amnion, 4 of calcium alginate got infected. Average healing duration was 11 days in Group A; and it was 14 days in Group B (p-value = 0.000). Conclusion: Amnion shows quicker healing and better pain control than calcium alginate.